Real-world experience of galcanezumab in the prevention of migraine in Spain: a systematic literature review - Pozo-Rosich, Patricia; García-Azorín, David; Díaz-Cerezo, Silvia; Fernández-Montoya, Julia; de Paz, Héctor David; Núñez, Mercedes (Frontiers in Neurology, 2024)
IntroductionIn the context of migraine preventive therapy, new therapeutic modalities such as monoclonal antibodies targeting the calcitonin gene-related peptide receptor (CGRP) or ligand offer potential advantages over traditional preventive treatments.MethodsThis systematic literature review gathered recent real-world evidence from Spain on the use of galcanezumab, a CGRP-targeting treatment, in migraine patients. The review included observational studies in English or Spanish, published from August 2020 to August 2023, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and Cochrane guidelines.ResultsA total of 29 publications involving 2,592 Spanish adult patients were identified, reporting relevant information on clinical outcomes (treatment effectiveness and safety), treatment persistence and patterns (switching from other therapies and time to discontinuation and restart), and patient-reported outcomes (including satisfaction with treatment). The most frequently reported variables were related to the clinical effectiveness of galcanezumab, demonstrating a significant reduction in monthly migraine days and monthly headache days. Additionally, adverse impact of headache per HIT-6 (Headache Impact Test-6) and disability per MIDAS (Migraine Disability Assessment) also improve. Studies also showed that up to 12-month persistence to galcanezumab ranged from 76.8 to 59.8%. Serious adverse events were rare. None of the publications included health-related quality of life data, either generic or migraine-specific. One study highlighted that galcanezumab treatment would offer high patient satisfaction for people with migraine.ConclusionThe real-world evidence on the use of galcanezumab treatment among the Spanish population shows that its effectiveness, persistence, safety, and impact on health burden align with findings from clinical trials and observational studies conducted in other countries. Future studies should incorporate health-related quality of life data to gain a more holistic understanding of this treatment’s impact.